Transformation of Policing: The Role of Criminal Intelligence - Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
Policing in Serbia is currently going through a period of significant change in both operational tactics and organisational structures. Intelligence-led policing represents the worldwide more prevalent approach to crime control philosophy and policing practice. The article ends by arguing that strategic criminal intelligence forecasts about future crime trends that emanate from the police sector are the only way towards future good outcomes in the sense of efficient and effective policing in Serbia.